2021
DOI: 10.2217/pme-2019-0141
|View full text |Cite
|
Sign up to set email alerts
|

PON1 Polymorphisms Can Predict Generalized Anxiety and Depressed Mood in Patients with Multiple Chemical Sensitivity

Abstract: Background: Multiple chemical sensitivity (MCS) is a chronic condition with somatic, cognitive and affective symptoms that follow contact with chemical agents at usually non toxic concentrations. We aimed to assess the role of genetic polymorphisms involved in oxidative stress on anxiety and depression in MCS. Materials & methods: Our study investigated the CAT rs1001179, MPO rs2333227, PON1 rs662 and PON1 rs705379 polymorphisms in MCS. Results: The AG genotype of the PON1 rs662 and the TT and CT genotypes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 109 publications
0
3
0
Order By: Relevance
“…The influence of the paraoxonase 1 (PON1) polymorphisms, which affect the formation of ROS/RNS and the immuno-inflammatory characteristics of depression, has also been discussed [ 45 , 46 ]. Similarly, the PON1 polymorphism has been associated with depression and anxiety in individuals who are sensitive to contact with chemicals of nontoxic concentrations [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The influence of the paraoxonase 1 (PON1) polymorphisms, which affect the formation of ROS/RNS and the immuno-inflammatory characteristics of depression, has also been discussed [ 45 , 46 ]. Similarly, the PON1 polymorphism has been associated with depression and anxiety in individuals who are sensitive to contact with chemicals of nontoxic concentrations [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The historic lack of understanding of the underlying biomechanisms for CI has inappropriately fostered a view of CI as a psychosomatic disorder (e.g., Multiple Chemical Sensitivity) [59]. However, the psychosomatic view of CI has diminished over time due in part to a greater understanding of the roles of gene-environment interactions, oxidative stress processes, olfactory and sensory pathways, and systemic inflammation in CI [60][61][62][63]. In addition to avoiding symptom triggers, other treatment options have been identified, and while evidence-based treatments are not yet available, multidisciplinary integrative care models have been suggested [64][65][66][67][68].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, there has been a significant relationship with the Superoxide Dismutase 2 (SOD2) [ 2 ]. Another study found that PON1 polymorphisms may play an additional role in patients with MCS who also have anxiety and depression [ 8 ].…”
Section: Introductionmentioning
confidence: 99%